Pengembangan Kemandirian Kelompok Difabel Melalui Pemanfaatan Pemasaran Digital di Kota Magelang - Lintang Citra Christiani; Prinisia Nurul Ikasari; Fitria Khairum Nisa (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Different physical or nonphysical conditions bring the disabled group into the depletion chain, both socially, politically, and economically. It started from the low access to education to low uptake in the industrial world. The effort to break the depletion chain is to develop the self-sufficiency of children with disabilities and independence from the Gerakan untuk Kesejahteraan Tunarungu Indonesia (Gerkatin) through the guidance of digital marketing utilization. The empowerment approach is used in this activity from the start of planning activities, implementation, to evaluation through participatory methods and learning by doing. From the results of community devotion activities, the target group becomes more economically independent with digital marketing skills and shifting the gadget addiction to more rewarding online activities. The formation of Magelang Disabled Digital Interprenenur Community is an effort to ensure the continuity of the program.